Comparison of Exo-Seal(®) and Angio-Seal (®) for arterial puncture site closure: A randomized, multicenter, single-blind trial - Ketterle, Johannes; Rittger, Harald; Helmig, Inga; Klinghammer, Lutz; Zimmermann, Stefan; Hohenforst-Schmidt, Wolfgang; Brachmann, Johannes; Nef, Holger; Achenbach, Stephan; Schlundt, Christian (Herz, 2015)
The use of extravascular femoral closure devices in patients undergoing coronary angiography/intervention has not been sufficiently evaluated. We sought to define the impact of an extravascular polyglycolic acid (PGA) plug for the closure of a femoral access site in patients undergoing coronary angiography and/or percutaneous coronary intervention.In this prospective, single-blind, multicenter trial we randomly assigned 319 patients to vessel closure with Angio-Seal(®) or Exo-Seal(®). We hypothesized that the use of an extravascular closure device is not inferior to an anchor/plug-mediated device regarding the occurrence of the composite primary endpoint: hematoma > 5 cm, significant groin bleeding (TIMI major bleed), false aneurysm, and device failure.There was no significant difference in patient baseline characteristics or procedural results. After 24 h the primary endpoint occurred in nine patients (5.6 %) in the Angio-Seal(®) group and in 13 patients (8.2 %) inthe Exo-Seal(®) group (p = 0.38). Hematoma > 5 cm was noted in three patients (1.9 %) receiving Angio-Seal(®) vs. two patients (1.3 %) receiving Exo-Seal(®) (p = 0.99). In one patient (0.6 %) of the Exo-Seal(®) group, TIMI major bleeding occurred, requiring transfusion (p = 0.49). There were four (2.5 %) false aneurysms found in patients treated with Angio-Seal(®) and two (1.3 %) in patients treated with Exo-Seal(®) (p = 0.68). There was a trend for a higher incidence of device failure in the Exo-Seal(®) group (1.2 vs. 5.2 %, p = 0.06). At telephone interview after 30 days, there was no significant difference found regarding the events readmission with surgery of puncture site, infection, bleeding, hematoma, or pain.In the present study, there were no significant differences found regarding the occurrence of hematoma > 5 cm, major bleeding, false aneurysm, and device failure between Angio-Seal(®) and Exo-Seal(®) 24 h after device implantation.
EVALuna2:12086